Tire and vehicle dynamics - Pacejka, H. B. (Butterworth-Heinemann ; Distributed in conjunction with SAE International, 2012)
The definitive book on tire mechanics by the acknowledged world expert Covers everything you need to know about pneumatic tires and their impact on vehicle performance, including mathematic modeling and its practical application Written by the acknowledged world authority on the topic and the name behind the most widely used model, Pacejka's 'Magic Formula' Updated with the latest information on new and evolving tire models to ensure you can select the right model for your needs, apply it appropriately and understand its limitations In this well-known resource, leading tire model expert Hans Pacejka explains the relationship between operational variables, vehicle variables and tire modeling, taking you on a journey through the effective modeling of complex tire and vehicle dynamics problems. Covering the latest developments to Pacejka's own industry-leading model as well as the widely-used models of other pioneers in the field, the book combines theory, guidance, discussion and insight in one comprehensive reference. While the details of individual tire models are available in technical papers published by SAE, FISITA and other automotive organizations, Tire and Vehicle Dynamics remains the only reliable collection of information on the topic and the standard go-to resource for any engineer or researcher working in the area. New edition of the definitive book on tire mechanics, by the acknowledged world authority on the topicCovers everything an automotive engineer needs to know about pneumatic tires and their impact on vehicle performance, including mathematic modelling and its practical applicationMost vehicle manufacturers use what is commonly known as Pacejka's 'Magic Formula', the tire model developed and presented in this book.
Keywords: Tires -- Performance.; Motor vehicles -- Dynamics.; Motor vehicles -- Tires.; Tires -- Traction.; elektronické knihy; electronic books